AUTHENTIC LITERATURE AND TECHNOLOGY INVOLVEMENT IN EFL READING - Bastian Sugandi (International Conference on Education and Language (ICEL), 2016)
This article comes up with the problems that are faced by the students in reading class. They are dealing with students’ interest and motivation in reading. Most of students are uninterested and unmotivated to read since most of teachers usually use only a single textbook in teaching reading. In fact, students’ interests in reading are various, so it will be better if the teacher use various texts in teaching reading. There are six types of texts for reading instruction; one of them is authentic literature. Authentic literature refers to narrative and expository texts that are written in the original and natural language of the authors. It is often refers as “real books” or “trade books”, such as magazine, novel, newspaper, comic etc. Technology, especially internet websites, presents the opportunities for authentic materials, as well as access to a wealth of ready-made ELT materials. This paper aims at emphasizing the use of authentic literature and internet websites in teaching EFL reading.